The Role of Fibroblast Growth Factor 19 Subfamily in Different Populations Suffering From Osteoporosis - Yu, Xiawen; Xia, Yue; Jia, Jue; Yuan, Guoyue (Frontiers in Endocrinology, 2022)
Fibroblast growth factor (FGF) 19 subfamily, also known as endocrine fibroblast growth factors (FGFs), is a newly discovered metabolic regulator, including FGF19, FGF21 and FGF23. They play significant roles in maintaining systemic homeostasis, regulating the balance of bile acid and glucolipid metabolism in humans. Osteoporosis is a chronic disease, especially in the current status of aging population, osteoporosis is the most prominent chronic bone disease, leading to multiple complications and a significant economic burden that requires long-term or even lifelong management. Members of the FGF family have been shown to be associated with bone mineral density (BMD), fracture repair and cartilage regeneration. Studies of the FGF19 subfamily in different populations with osteoporosis have been increasing in recent years. This review summarizes the role of the FGF19 subfamily in bone metabolism, and provides new options for the treatment of bone diseases such as osteoporosis.